2022
DOI: 10.1177/00034894221088180
|View full text |Cite
|
Sign up to set email alerts
|

Health and Well-Being Needs Among Head and Neck Cancer Caregivers – A Systematic Review

Abstract: Objective: This review provides a summary of the current understanding of the health and well-being of the head and neck cancer (HNC) caregiver. Our goal is to understand the healthcare needs required by the caregivers of our oncologic patients, which may ultimately influence quality of care and support that cancer patients require during treatment and recovery. Methods: Independent database searches were conducted to identify articles describing HNC caregiver health and healthcare utilization. Search terms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…In addition, reviews on the topic highlight the disproportionate number of female caregivers compared with males. 71 The use of screening tools may be helpful adjuncts to assess caregiver burnout. The Caregiver Strain Index and Caregiver Quality of Life Index are two tools previously used to assess caregiver burden in the head and neck cancer population.…”
Section: Caregiver Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, reviews on the topic highlight the disproportionate number of female caregivers compared with males. 71 The use of screening tools may be helpful adjuncts to assess caregiver burnout. The Caregiver Strain Index and Caregiver Quality of Life Index are two tools previously used to assess caregiver burden in the head and neck cancer population.…”
Section: Caregiver Burnoutmentioning
confidence: 99%
“…In addition, reviews on the topic highlight the disproportionate number of female caregivers compared with males. 71…”
Section: Caregiver Burnoutmentioning
confidence: 99%
“…Seek appropriate mental health support, because surviving HNC leaves a trail of tears in your mind and body, often resulting in some type of PTSD. [5] Aspiration pneumonia awareness. This is common among HNC survivors.…”
Section: Part II Quality-of Life (Qol) As a Survivormentioning
confidence: 99%
“…There are several studies measuring ICs' well-being regarding caregiver burden (e.g. Benyo et al, 2022;Wang et al, 2021;Castellanos et al, 2019;Thana et al, 2020). Caregiver burden can be described as a multidimensional biopsychosocial reaction resulting from an imbalance between care demands and a caregiver's care resources (Given et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Caregiver burden can be described as a multidimensional biopsychosocial reaction resulting from an imbalance between care demands and a caregiver's care resources (Given et al, 2001). It has previously been described that ICs of individuals with HNC often report depression, fatigue and sleep disturbance due to the caregiver burden they experience (Benyo et al, 2022). A systematic review performed by Wang et al (2021) identified unmet needs among ICs of individuals with HNC regarding information about the illness and its treatment.…”
Section: Introductionmentioning
confidence: 99%